BULLYING BEHAVIOUR IN OPERATING THEATRES - Iqbal, Almas; Khattak, Afshan; Malik, Farhat R (Journal of Ayub Medical College Abbottabad, 2020)
Background Bullying is a well-recognized negative behaviour, involving a perpetrator and a victim, with negative physical and/or psychological consequences. Bullying, as a multifaceted form of mistreatment, came to the attention of academic and administrative teams in schools and the workplace, more than three decades ago. Workplace bullying is well recognized to lead to anxiety, depression, feeling of helplessness, higher risks of cardiovascular disease and suicidal ideation among its victims. Healthcare teams face high odds and challenging roles in intensive care units and operating theatres. The objective of the study was to determine the prevalence of bullying behaviour through (Revised), Negative Attitudes Questionnaire (NAQ-R), among healthcare team members in an operating theatre of a Tertiary Care hospital in Lahore Methods A cross-sectional pilot study was conducted, through a validated tool, Negative Attitude Questionnaire-Revised (NAQ-R). An online survey was posted through Survey Monkey. Data analysed through SPSS Version- 19 by computing descriptive statistics as frequency and percentages with graph construction. Results One hundred thirty-one complete responses received out of 139 with a response rate of 94.24%. Responses were from both government (53%) and private sector (47%) hospitals. Norway cut off values used for analysis. Overall, 32% were not bullied whereas 68% were bullied, 47.6% were victims of bullying frequently and rest occasionally. Bullying behaviour across gender confirmed higher frequency in women as compared to men (83% vs 58%) with frequent bullying also more common in women when compared with males (51% versus 18%). Conclusion Bullying occurs in both genders although, predominantly more among women Keywords: Bullying; Behaviour; Gender; Pilot Study; Anxiety; Depression; Prevalence; Aggression; Female; NAQ- R